2006
DOI: 10.1039/b602548j
|View full text |Cite
|
Sign up to set email alerts
|

Star-shaped block copolymer stabilized palladium nanoparticles for efficient catalytic Heck cross-coupling reactions

Abstract: Palladium nanoparticles of improved stability against aggregation were prepared using 5-arm star-shaped block copolymers with a poly(ethylene oxide) (PEO) core and a poly(e-caprolactone) (PCL) corona as templates. The PEO core of these star-shaped block copolymers could be swollen with palladium acetate (Pd(OAc) 2 ) in N,N-dimethylformamide (DMF), and Pd nanoparticles were obtained by reduction with NaBH 4 . This procedure resulted in well defined Pd nanoparticles that were stabilized against aggregation due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 20 publications
0
37
0
1
Order By: Relevance
“…[73] The PEO core was swelled with Pd(OAc) 2 in N,N-dimethyl-formamide (DMF), and Pd NPs were obtained by reduction with NaBH 4 . Transmission electron microscopy studies strongly suggested that one Pd NP was formed inside each star-shaped block copolymer.…”
Section: Polymer-stabilized Npsmentioning
confidence: 99%
“…[73] The PEO core was swelled with Pd(OAc) 2 in N,N-dimethyl-formamide (DMF), and Pd NPs were obtained by reduction with NaBH 4 . Transmission electron microscopy studies strongly suggested that one Pd NP was formed inside each star-shaped block copolymer.…”
Section: Polymer-stabilized Npsmentioning
confidence: 99%
“…[4] This uniquely versatile and powerful chemical has been used as a solvent in a wide variety of synthetic procedures, including: preparation of colloids, [5][6][7] synthesis of block-copolymers, [8,9] and many types of organic chemistry reactions. [10] The important role played by DMF as a solvent and reaction medium has motivated studies related to its redox activity.…”
Section: Redox Chemistry Of Dmfmentioning
confidence: 99%
“…In addition, hyperbranched polymers can be used for the preparation of polymeric core-shell architectures [14,15] opening application possibilities as drug-delivery systems [16,17] due to their encapsulation behaviors [18,19] in a similar fashion as dendrimers [20,21] or star-shaped block copolymers. [22,23] Moreover, such coreshell macromolecules were shown to stabilize metalnanoparticles, [24,25] act as catalysts, [26,27] or enable sensoric applications. [28,29] Due to these interesting and manifold application possibilities of branched macromolecules and the lack of knowledge regarding the preparation of hyperbranched polymers via ADMET type metathesis chemistry, we investigated the ATMET of triglyceride 1 with different amounts of methyl acrylate (MA) as a chain stopper in order to prevent full cross-linking of 1 and to obtain branched polymers of different molecular weights in a straightforward one step one pot approach.…”
Section: Introductionmentioning
confidence: 99%